2023
DOI: 10.1084/jem.20220839
|View full text |Cite
|
Sign up to set email alerts
|

Stability and heterogeneity in the antimicrobiota reactivity of human milk-derived immunoglobulin A

Abstract: Immunoglobulin A (IgA) is secreted into breast milk and is critical for both protecting against enteric pathogens and shaping the infant intestinal microbiota. The efficacy of breast milk–derived maternal IgA (BrmIgA) is dependent upon its specificity; however, heterogeneity in BrmIgA binding ability to the infant microbiota is not known. Using a flow cytometric array, we analyzed the reactivity of BrmIgA against bacteria common to the infant microbiota and discovered substantial heterogeneity between all dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Sequencing of IgA‐bound and unbound bacteria revealed that NEC was associated with increasing domination by Enterobacteriaceae in the unbound fraction prior to disease onset, providing a mechanistic understanding of how maternal IgA shapes host‐microbiota interactions in preterm neonates. Interestingly, a follow‐up longitudinal study demonstrated that the antimicrobial activity of breastmilk‐derived IgA is heterogenous among lactating mothers, but relatively stable within the same individual 28 . This intriguing observation raises questions about which signals are controlling the composition of breastmilk IgA and/or other antibodies.…”
Section: Overview Of Mechanisms Influencing Maternal‐offspring Immune...mentioning
confidence: 99%
“…Sequencing of IgA‐bound and unbound bacteria revealed that NEC was associated with increasing domination by Enterobacteriaceae in the unbound fraction prior to disease onset, providing a mechanistic understanding of how maternal IgA shapes host‐microbiota interactions in preterm neonates. Interestingly, a follow‐up longitudinal study demonstrated that the antimicrobial activity of breastmilk‐derived IgA is heterogenous among lactating mothers, but relatively stable within the same individual 28 . This intriguing observation raises questions about which signals are controlling the composition of breastmilk IgA and/or other antibodies.…”
Section: Overview Of Mechanisms Influencing Maternal‐offspring Immune...mentioning
confidence: 99%
“…IgA-producing plasma cells traffic from the Peyer's Patches and intestine to the mammary glands during pregnancy (23)(24)(25)(26). The anti-bacterial reactivity of breast milk IgA is highly heterogeneous between individuals but stable over time, which highlights a drawback of 'vertically transmitted' immunity, that it is not responsive to the conditions of the infant's intestine (27). There are potential consequences for the infant of 'holes' in the anti-bacterial antibody repertoire, most notably an increased susceptibility to enteric pathogens (17,18,28) and a reduction in IgA binding to Enterobacteriaceae is associated with the development of Necrotizing Enterocolitis in preterm infants (11).…”
Section: Introductionmentioning
confidence: 99%